РОЗРАХУНОК ПОХИБКИ ЄМНІСНОГО СЕНСОРА ПОВІТРЯНОГО ПРОМІЖКУ В ГІДРОГЕНЕРАТОРАХ З СИСТЕМОЮ КОМПЛАНАРНИХ ЕЛЕКТРОДІВ, ЗУМОВЛЕНОЇ ПЕРЕКОСОМ - А.С. Левицький; Є.О. Зайцев; В.Л. Рассовський; С.А. Закусило (Праці Інституту електродинаміки Національної академії наук України)
In this paper calculating the technological errors that arise when using capacitive sensors to measure the air gap (AG) in hydrogen generators, in particular, those caused by the inaccuracy of their installation on the machine. The results of the analysis of the error caused by the skew of the plane of the sensor electrodes relative to the constructive boring of the stator core are given. It was found that the skew of the electrodes could significantly affect the accuracy of the measurements, which in turn affects the efficiency and reliability of the hydrogen generator. A detailed assessment of the influence of this skew on the measurement results was carried out using a sensor consisting of a system of N copla-nar parallel strip electrodes located perpendicular to the core boring. A calculation scheme has been developed for the quantitative assessment of the error, which allows determining the value of the error taking into account analytical dependencies. Numerical methods were used to assess the influence of skew on the accuracy of measurements, and the results were obtained for a sensor designed for a capsule hydrogen generator of the SGK538/160-70M type. Based on the obtained results, practical recommendations have been developed to reduce the impact of skew error on measurement accuracy. Ref. 11, fig. 6.